A cloud‐based integration platform for enterprise application integration: A Model‐Driven Engineering approach. (27th October 2020) - Frantz, Rafael Z.; Corchuelo, Rafael; Basto‐Fernandes, Vitor; Rosa‐Sequeira, Fernando; Roos‐Frantz, Fabricia; L. Arjona, José
Abstract: This article addresses major information systems integration problems, approaches, technologies, and tools within the context of Model‐Driven Software Engineering. The Guaraná integration platform is introduced as an innovative platform amongst state‐of‐the‐art technologies available for enterprises to design and implement integration solutions. In this article, we present its domain‐specific modeling language and its industrial cloud‐based web development platform, which supports the design and implementation of integration solutions. A real‐world case study is described and analyzed; then, we delve into its design and implementation, to finally disclose ten measures that empirically help estimating the amount of effort involved in the development of integration solutions.